Estrategias para desarrollar el pensamiento creativo dirigidos a niños y niñas de 5 a 7 años. - Guamba Verdejo, Verónica Elizabeth (2014)
The present investigation has as its basic objective the elaboration of a Guide for the Development of Creative Thought for children in Basic General Education. In this way, we aim to show the importance of the development of creative thought in education. Various authors propose different correct, but not unique, definitions of creativity. Creativity values originality, flexibility, and imagination in the search for, and solving of, problems. While thought is a form of expressing one’s ideas, it is also a situation of interaction with others. Relating creativity and thought, one can say that creativity is a part of thought. Thus creativity is a way of communicating by way of reflective and analytic thought that tends to be original. It must be kept in mind that teachers should be oriented towards the evolution of each of their students and to come to know the characteristics which enter into learning and teaching. In early childhood, language is fundamental, a means of expression.